Diabetes Does Not Adversely Affect Neurological Recovery and Reduction of Neck Pain After Posterior Decompression Surgery for Cervical Spondylotic Myelopathy: Results From a Retrospective Multicenter Study of 675 Patients. Issue 7 (1st April 2021) - Nori, Satoshi; Nagoshi, Narihito; Yoshioka, Kenji; Nojiri, Kenya; Takahashi, Yuichiro; Fukuda, Kentaro; Ikegami, Takeshi; Yoshida, Hideaki; Iga, Takahito; Tsuji, Osahiko; Suzuki, Satoshi; Okada, Eijiro; et al.
Abstract : Study Design: Retrospective multicenter study. Objective: The aim of this study was to identify the impact of diabetes on surgical outcomes of posterior decompression for cervical spondylotic myelopathy (CSM). Summary of Background Data: Although some previous studies have reported surgical outcomes of posterior decompression for CSM in diabetic patients, their results were inconsistent. Methods: We included 675 patients with CSM who underwent posterior decompression. Patients were divided into diabetic (n = 140) and nondiabetic (n = 535) groups according to the diabetic criteria for glucose intolerance. Surgical outcomes as assessed by the Japanese Orthopedic Association (JOA) scores and visual analog scale (VAS) for neck pain were compared between groups. Subsequently, the functional outcomes of diabetic patients were compared between the mild (n = 131) and moderately severe (n = 9) groups. All patients were followed up for at least 1 year after surgery. Results: Compared with the nondiabetic group, the diabetic group showed lower pre- and postoperative JOA scores ( P = 0.025 and P = 0.001, respectively) and a lower JOA score recovery rate (RR) ( P = 0.009). However, the preoperative-to-postoperative changes in JOA scores in the diabetic and nondiabetic groups were not significantly different ( P = 0.988). Pre- and postoperative VAS for neck pain and postoperative reduction of neck pain were comparable between groups ( P = 0.976, P = 0.913 and P = 0.688, respectively). Although statistical analysis was not performed due to the small underpowered sample size, functional outcomes assessed by the JOA score RR (43.3 ± 37.1% vs. 45.3 ± 33.9%) and preoperative-to-postoperative changes in JOA scores (3.0 ± 2.2 vs . 2.7 ± 2.5) were similar between the mild and moderately severe diabetes groups. Conclusion: CSM patients with diabetes experienced improvements in neurological function and neck pain as a result of posterior decompression to the same extent seen in patients without diabetes. Level of Evidence: 3 Abstract : A retrospective multicenter study revealed the impact of diabetes on surgical outcomes of posterior decompression for cervical spondylotic myelopathy. The Japanese Orthopedic Association scores and visual analog scale scores for neck pain were not different between diabetic and nondiabetic patients. Posterior decompression is effective regardless of diabetic comorbidity.